Development and Current Status of National Cancer Center for Chinese Medicine - 李杰 林洪生 侯炜 张培彤 花宝金 (Chinese journal of integrative medicine, 2011)
Chinese medicine （CM） is an important feature of cancer treatment in China. Especially in the last 10 years, the effect of CM in cancer treatment has been of high concern and has been accepted by experts and patients locally and overseas. The oncology department （OD） of Guang＇anmen Hospital （GAMH） of China Academy of Chinese Medical Sciences （CATCM）, which will mark its 50th anniversary in 2013, is one of China＇s most-respected centers devoted exclusively to cancer patient care, research, education, and prevention through CM. It is located at the campus of GAMH, central Beijing.